Ageing & Sports - Seuthe J; Hulzinga F; D'Cruz N; Ginis P; Nieuwboer A; Schlenstedt C (Dynamic Media Sales Verlag, 2021)
Exercise has become increasingly relevant in the treatment of people with Parkinsons Disease (PD), especially for gait and balance impairments where pharmacological and surgical therapy does not fully alleviate symptoms. Split-belt treadmill (SBT) is a tool which can introduce artificial asymmetry and motor switches through belts running at different velocities and has been used to study motor control or as exercise intervention. This narrative review summarizes the current literature of SBT as a therapeutic tool for people with PD. Studies have shown that walking on an SBT is safe and feasible for people with PD and results suggest that training should best be carried out under antiparkinsonian medication. Compared to healthy adults, people with PD adapt their gait in a similar manner during and after SBT walking, but effects are smaller. One session of SBT training improved gait adaptation as well as gait during dual tasking, with results being partially retained for 24 hours. With regard to endurance, tendencies are visible that SBT training has generic health benefits similiar to aerobic exercise.Further studies are ongoing investigating long term training interventions of SBT in people with PD, including the study of retention effects.  However, the clinical relevance of the above-mentioned benefits remains unclear. Finally, the aerobic benefit of the training and the potential for alleviation of fall risk in the PD population need to be investigated.Key Words: Rehabilitation, Gait Disorder, Neurological Disease, Exercise Therapy